Analysis of the Dynamics of Some Economic Indicators for Latvia in the Period Before and After Joining the Euro Area - Kaneva, Aglika (Research Papers, 2025)
In this paper, the change in some economic indicators for Latvia from joining the European Union in 2004 to 2023, including the adoption of the euro in 2014, have been analyzed. The real convergence of the country to the European Union economy has been studied. The impact of euro adoption in Latvia on the economic indicators included in the paper has been examined.
Keywords: HIPC; Latvia; Economic indicators; Real convergence; Euro area